Time‐lapse microscopy of oxidative stress demonstrates metabolic sensitivity of retinal pericytes under high glucose condition. Issue 9 (8th June 2018) - Ghanian, Zahra; Mehrvar, Shima; Jamali, Nasim; Sheibani, Nader; Ranji, Mahsa
Abstract : Hyperglycemia affects retinal vascular cell function, promotes the development and progression of diabetic retinopathy and ultimately causes vision loss. Oxidative stress, reactive oxygen species (ROS) in excess, is a key biomarker for diabetic retinopathy. Using time‐lapse fluorescence microscopy, ROS dynamics was monitored and the metabolic resistivity of retinal endothelial cells (REC) and pericytes (RPC) was compared under metabolic stress conditions including high glucose (HG). In the presence of a mitochondrial stressor, REC exhibited a significant increase in the rate of ROS production compared with RPC. Thus, under normal glucose (NG), REC may utilize oxidative metabolism as the bioenergetic source, while RPC metabolic activity is independent of mitochondrial respiration. In HG condition, the rate of ROS production in RPC was significantly higher, whereas this rate remained unchanged in REC. Thus, under HG condition RPC may preferentially utilize oxidative metabolism, which results in increased rate of ROS production. In contrast, REC use glycolysis as their major bioenergetic source for ATP production, and consequently HG minimally affects their ROS levels. These observations are consistent with our previous studies where we showed HG condition has minimal effect on apoptosis of REC, but results in increased rate of apoptosis in RPC. Collectively, our results suggest that REC and RPC exhibit different metabolic activity preferences under different glucose conditions. Thus, protection of RPC from oxidative stress may provide an early point of intervention in development and progression of diabetic retinopathy. Abstract : Oxidative stress (OS) is measured in two retinal vascular cell types, retinal pericytes (RPC) and endothelial cells (REC). Fluorescence time‐lapse microscopy of live cells tagged with nano‐molar MitoSOX is used for online monitoring of OS. Temporal metabolic responses of RPC and REC are compared under different metabolic stress and different glycemic conditions. The experimental results show the cell‐type differential metabolic response and the potential to study the cell‐type preferential metabolic pathway.